Anticipation Effects of EU Accession on Immigrants' Labour Market Outcomes - Alberto Dalmazzo; Roberto Leombruni; Tiziano Razzolini (Institute of Labor Economics (IZA), 2023)
Regulations in host countries often impose heavy limitations on the opportunities of migrant workers. Here, we analyse how (the anticipation of) a change in the legal status of foreign workers may affect their terms of employment. Building on a simple theoretical model, we consider a sample of non-EU immigrants in Italy over the period which led to the accession of Romania and Bulgaria to the European Union in 2007. We find that the expectation of achieving EU citizenship increased Romanians' and Bulgarians' bargaining power over wages and job attributes, relative to other non-EU migrants, and also stimulated business venture.
Keywords: J28; J32; J71; 330; migration; labor market restrictions; EU accession; workplace safety